Plau and Tgfbr3 are YAP-regulated genes that promote keratinocyte proliferation. Issue 11 (November 2018) - Corley, Susan; Mendoza-Reinoso, Veronica; Giles, Nichole; Singer, Emma; Common, John; Wilkins, Marc; Beverdam, Annemiek
Abstract Yes-associated protein (YAP) is a mechanosensor protein and a downstream effector of the Hippo kinase pathway, which controls organ growth, cell proliferation, survival, maintenance and regeneration. Unphosphorylated YAP translocates to the nucleus where it acts as a cofactor of primarily the TEAD transcription factors to activate target gene transcription and cell proliferation. Perturbed YAP activation results in tumorigenesis. The pathways downstream of activated YAP that drive cell proliferation remain relatively unexplored. In this study, we employed YAP2-5SA-∆C transgenic mice, which overexpress a mildly activated YAP mutant protein in basal keratinocytes leading to increased proliferation of the epidermal stem/progenitor cell populations. We performed massively-parallel sequencing of skin biopsy mRNA (RNA-Seq) and found dysregulation of 1491 genes in YAP2-5SA-∆C skin, including many with roles in cell activation and proliferation. Furthermore, we found that 150 of these dysregulated genes harbored YAP/TEAD binding motifs in the 3′ UTR, suggesting that these may be direct YAP/TEAD target genes in the control of epidermal regeneration. Further validation and functional characterization assays identifiedPlau andTgfbr3 as prime candidate genes that may be activated by epidermal YAP activity in the mouse skin in vivo to promote keratinocyte proliferation. This study provides novel insights into the mechanisms regulated by YAP that control tissue homeostasis, and in particular in conditions where YAP is aberrantly activated such as in neoplastic and regenerative skin disease.